DINAMIKA PENGASUHAN AYAH BEKERJA: KETERLIBATAN AYAH DENGAN PERKEMBANGAN SOSIAL ANAK PRASEKOLAH - Vivi Irzalinda; Intan Vanesa; Yulina Eva Riany (Universitas Hamzanwadi, 2023)
Paternal parenting has received a lot of attention from researchers all over the world. However, many parents are unaware of how the father's role influences a child's development. The purpose of this study was to analyze the relationship between the practice of father involvement in parenting and the relationship between fathers and children, as well as the social development of preschoolers. The research method uses quantitative methods with a total of 60 respondents. Respondents are working families (dual earners) with early childhood aged 5-6 years. The research location is Tempuran Village, Trimurjo District, Lampung Tengah Regency. Data collection techniques using interviews. Data analysis technique using correlation test. The results of the analysis found that the practice of father involvement in parenting and father-child relationships was in the high category, and the social development of children was in the low category. There is a significant positive relationship between the practice of father involvement in parenting and the father-child relationship, and children's social development. In addition, there is a significant relationship between the practice of father involvement in parenting with the dimensions of socialization and responsibility. Keywords: practice of father involvement in parenting, father-child relationship, social development of child, dimensions of socialization